Neue Stimmen 2005 - 11. Internationaler Gesangswettbewerb - Sanchez Lansch, Enrique; Ciniselli, Michael; Darlington, Jonathan; Aglatova, Anna; Archibald, Jane; Savastano, María Virginia (Neue Stimmen, 2006)
Die CD enthält einen Live-Mitschnitt vom Finalkonzert am 21./22. Oktober 2005.